Functional properties of β-glucosidase-producing Lactobacillus plantarum SC 359 isolated from Thai fermented soybean food - Sirilun,S. (Akademiai Kiado, 2015)
The aims of this study were to isolate LAB from Thai plant-derived foods and beverages and to examine in vitro probiotic properties including b-glucosidase enzyme activity. Lactobacillus plantarum SC 359 selected from Thai pickled soybean was significantly (P<0.05) the best to perform β-glucosidase enzyme activity (0.396 U ml-1 at 18 h of incubation) out of the 227 tested strains. The strain survived in 0.30% (w/v) bile salt and had high tolerance to acidic pH with survival rates at a 2 h period of 72.24%, 85.52%, 92.64%, and 93.38% at pH 2.0, 3.0, 4.0, and 5.0, respectively. The SC 359 strain showed proteolytic and lipolytic activities. Moreover, the selected strain displayed strong antagonistic activities against Bacillus cereus ATCC 11778, Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 25923, Pseudomonas aeruginosa ATCC 27853, Salmonella Typhi, Shigella sonnei and Candida albicans ATCC 90028. The strain was susceptible to ampicillin, chloramphenicol, erythromycin, gentamicin, kanamycin, rifampicin, streptomycin, tetracycline, and vancomycin. In addition, the selected strain significantly inhibited the adherence to Caco-2 cells of E. coli, S. Typhi and Sh. sonnei (P<0.05) by 33.50 to 73.37%. The strain could obstruct the adherences of pathogens by elimination, competition, and displacement with pathogen adherences 33.62-53.92%, 26.63-59.23%, and 49.41-66.50%, respectively. Based on the results, the selected strain could be applied as functional starter for Thai fermented plant-derived foods and beverages.